IMPROVING METHODS FOR ENRICHING NEW GENERATION TEXTBOOKS WITH MODERN SKILLS. - Muhammad Yunus Azam (TADQIQOTLAR, 2025)
Annotation: This article explores innovative methods for integrating modern skills, such as digital literacy, critical thinking, and collaboration, into next-generation textbooks. By combining insights from educational research and technological advancements, it proposes a framework for designing textbooks that prepare students for 21st-century challenges. The study includes a literature analysis, proposed methods, results from a pilot implementation, and recommendations for future textbook development.